2021
DOI: 10.1037/adb0000595
|View full text |Cite
|
Sign up to set email alerts
|

Identifying mechanisms that link pain to smoking relapse during a quit attempt.

Abstract: Objective: Emerging evidence suggests that adults with chronic pain have poor smoking cessation outcomes, but the exact mechanisms are less understood. This study examined whether depression, anxiety, stress, and then, positive outcome expectancy for smoking mediated the association between pain and smoking relapse during a quit attempt. Methods: This study is a secondary data analysis of a three-armed randomized clinical trial that compared in-person and smartphone-based smoking cessation interventions. Parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 72 publications
(120 reference statements)
1
0
0
Order By: Relevance
“…Evidence regarding influencing factors of relapse after quitting is essential to keep long-term abstinence. This survey showed that the first week after stopping smoking was the most likely time to relapse, which was consistent with previous studies 32 , 33 . Results indicate that the most frequent smoking relapse situations occurred when smokers were drinking alcohol.…”
Section: Discussionsupporting
confidence: 92%
“…Evidence regarding influencing factors of relapse after quitting is essential to keep long-term abstinence. This survey showed that the first week after stopping smoking was the most likely time to relapse, which was consistent with previous studies 32 , 33 . Results indicate that the most frequent smoking relapse situations occurred when smokers were drinking alcohol.…”
Section: Discussionsupporting
confidence: 92%